Mulheres na velhice : o peso da dupla exclusão em "O Planeta Desconhecido e Romance da Que Fui Antes de Mim", de Luísa Dacosta - Schwertner, Márcia Regina (2015)
From a trend based on memory as an instrument of identity construction, this research offers a reading of O planeta desconhecido e romance da que fui antes de mim by Portuguese writer Luísa Dacosta. When presenting the trajectory of Ana and Luísa, grandmother and granddaughter, Dacosta calls the attention to the dependence that follows old age and how physical and psychological form mix in a vicious circle marked by exclusion and seclusion. In this context, it is observed processes of exclusion faced by women, cognized by the contact with sickness and old age, since it is in frailty of the body that the protagonist define routes which lead her to the comprehension of herself. As theoretical approach, focusing on different perspectives related to the maintenance and construction of the past, it was studied works by Aleida Assmann and Paul Ricoeur, memory is seen not as a fixed process or likely to be completed, but as movement, continuous action done individually and collectively. Aiming at a dialogue between memory and identity, imaginary is an essential component, which took to a research of authors like Gaston Bachelard, Pierre Bourdieu and Michelle Perrot. This way, elements of the imaginary that act as activators of memory are approached, observing how, especially during the XIX Center, a feminine universe more restricted to the private environment was reinforced, and how it was marked by an overvaluation of youth and by idealization of marriage and loving relationship. In relation to Portuguese literature of the twentieth century, this research draws on works by Carlos Reis, Eduardo Lourenço, Jane Tutikian, Miguel Real and Simone Pereira Schmidt to mention but a few